Idea generation techniques in pop-up tourism labs - Yati Yati (Annals of Tourism Research Empirical Insights, 2023)
This study is the first of its kind - at least to the author's knowledge - that employs the knowledge creation theory to propose a new model of idea generation in short-term tourism innovation labs. This qualitative multi-case study explores six labs to reveal the elements of the idea generation techniques used in the labs. Furthermore, by modifying the existing knowledge creation process model, this study assembles the elements into a sequence. It shows that collaborative knowledge creation in tourism can potentially be enabled by employing techniques that include an informal introduction, individual thinking and presentations, group and plenary discussions, followed by a recapitulation at the end. The study offers a practical guide for designing idea generation techniques in tourism labs.
Keywords: 330; Idea generation technique; Innovation labs; Knowledge creation; Knowledge sharing; Tourism